2002
DOI: 10.1182/blood.v100.1.224
|View full text |Cite
|
Sign up to set email alerts
|

Repair of DNA interstrand crosslinks as a mechanism of clinical resistance to melphalan in multiple myeloma

Abstract: Melphalan is widely used as a preparative agent in patients with multiple myeloma (MM) undergoing autologous stem cell transplantation (SCT). Although disease relapse is the major cause of death after a melphalan-conditioned autograft, the mechanism remains unclear. Melphalan produces a number of DNA adducts with the DNA interstrand crosslink (ICL) considered to be the critical cytotoxic lesion. By using a modification of the single-cell gel electrophoresis (Comet) assay, we have measured formation and repair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
93
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(98 citation statements)
references
References 25 publications
5
93
0
Order By: Relevance
“…This can be used to measure crosslinking in lymphocytes or solid tumour material where samples are taken following treatment of patients with drugs such as ifosfamide , treosulfan (Corrie et al, 2005) or antibody directed enzyme pro-drug therapy (Webley et al, 2001). Alternatively, it can be used to measure crosslink formation and repair in cells isolated from patients and treated ex vivo with drug as in the present study, or as previously demonstrated in myeloma plasma cells treated with melphalan (Spanswick et al, 2002). In the latter study, myeloma cells from chemotherapy naïve patients were all incapable of repairing melphalan-induced crosslinks at 24 h after the peak of formation.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This can be used to measure crosslinking in lymphocytes or solid tumour material where samples are taken following treatment of patients with drugs such as ifosfamide , treosulfan (Corrie et al, 2005) or antibody directed enzyme pro-drug therapy (Webley et al, 2001). Alternatively, it can be used to measure crosslink formation and repair in cells isolated from patients and treated ex vivo with drug as in the present study, or as previously demonstrated in myeloma plasma cells treated with melphalan (Spanswick et al, 2002). In the latter study, myeloma cells from chemotherapy naïve patients were all incapable of repairing melphalan-induced crosslinks at 24 h after the peak of formation.…”
Section: Discussionmentioning
confidence: 52%
“…We have previously demonstrated that a modification of the single cell gel electrophoresis (comet) assay can be used successfully in the clinical setting to detect and quantify the levels of ICLs in patient lymphocytes and tumour cells at pharmacologically relevant doses of bifunctional alkylating agents Webley et al, 2001;Spanswick et al, 2002;Corrie et al, 2005). The method has also been used to measure cisplatin-induced ICLs in vitro (De Silva et al, 2002).…”
mentioning
confidence: 99%
“…It is now increasingly used to monitor ICL formation and unhooking in clinical samples (30,40) as a pharmacodynamic end point in clinical trials (41,42), and following ex vivo treatment (39,43).…”
Section: Discussionmentioning
confidence: 99%
“…The Comet assay allows measurement of DNA damage at a single-cell level. It has been modified to allow the sensitive detection and quantitation of DNA interstrand crosslinking and can be applied to both preclinical and clinical situations (Hartley et al, 1999a(Hartley et al, , b, 2004Spanswick et al, 2002). Comet assay results could only be obtained from a limited number of patients treated in this clinical study.…”
Section: Discussionmentioning
confidence: 99%